The impact of artificial intelligence on consumer behaviour and changes in business activity due to pandemic effects - Dias, T.; Gonçalves, R.; Lopes da Costa, R.; Pereira, L.; Dias, Á. (Human Technology, 2023)
The COVID-19 pandemic has impacted the world economy, and the restrictions have shaken business models. E-commerce has skyrocketed as the only way to purchase products and AI has received closer consideration as social distancing has become imperative. This research aims to find whether the COVID-19 has translated into an opportunity for the use of AI by companies. A survey incorporating consumers and companies was conducted to analyse the positioning of consumers regarding the use of AI, as well as the perception of companies regarding their possible use of AI. It was concluded that due to COVID-19 there was an increase in the relevance that companies give to AI, the main drivers being the companies' views on AI and the benefits from its use. Regarding consumer behaviour, consumers are more receptive to AI use, favouring a fully automated experience, with half of the sample preferring to buy online.